Nail psoriasis : a review of the literature - Schons, Karen Regina Rosso (2014)
Nails are considered epidermal appendages, and as such, are commonly affected in patients with psoriasis, 80% of whom are likely to develop nail psoriasis as a result of their condition. Two patterns of nail disorders have been shown to be caused by psoriasis. Nail matrix involvement can result in features such as leukonychia, pitting (punctures or cupuliform depressions), red spots in the lunula and crumbling. Nail bed involvement, on the other hand, can cause onycholysis, salmon or oil-drop patches, subungual hyperkeratosis and splinter hemorrhages. Nail disease causes aesthetic and functional impairment, and is indicative of more severe forms of psoriasis as well as of joint involvement. The treatment for nail psoriasis involves behavioral interventions, topical medications, or systemic therapy in case of extensive skin or joint involvement. This article presents a review of the main features of nail psoriasis, its clinical presentation, diagnostic and assessment methods, clinical repercussions, and of its available treatment options.